Employee’s satisfaction among expatriates in SCOPE International Sdn Bhd / Nur Hamizah Rusli - Rusli, Nur Hamizah (2010)
The research that has been done by the researcher is about Employee’s Satisfaction among expatriates in SCOPE International Sdn Bhd. In this research, the researcher will discuss several factors that contributed to the employee’s satisfaction in terms of their salary, working conditions and relationship between their colleagues as well. These three factors will affect employee’s satisfaction towards their job. The reason why the researcher chooses this topic is because, they want to see the correlation between those factors and employee’s satisfaction towards their job. Either it give a big impact or not to the organization. In this research, the sample would be all of the foreign workers in SCOPE which have five department including Trade, Securities, FMO and CRC. In a simple random sample ('SRS') of a given size, all such subsets of the frame are given an equal probability. Finally the researcher came out with result that failed to eject amount of salary and the researcher have to reject Ho office environment and relationship between colleagues.